SPOTLIGHT SURVEYS OF NEW GUINEA FRESHWATER CROCODILE (Crocodylus novaeguineae) IN MID-ZONE MEMBERAMO RIVER (MEMBERAMO AND ROUFFAER SYSTEMS), PAPUA PROVINCES - Kurniati, Hellen (ZOO INDONESIA, 2002)
Data hasil survei buaya